Aktivitas Antidiare Daun Harendong (Malestoma malabathricum L) - ika kurnia Sukmawati; Elin Yulinah Sukandar; Neng Fisheri Kurniati (State University of Gorontalo, 2020)
Diarrhea still become main health problem especially in several developing countries including Indonesia. Hharendong leaf have been used by people traditionally as the treatment of various Gastrointestinal tract disorders including diarrhea. The purpose of this study was tested antidiarrhea and antibacterial activity of extracts and fractions of the three selected plants. The extraction was conducted using reflux method with ethanol 96% as solvent. Extract was fractinated by liquid-liquid extraction methods using n-hexane and ethylacetate solvents gradually. Antimicrobial activity assays was performed by using broth microdiluiton methods toward extract and fractions of plants selected. Escherichia coli, Shigella dysenteriae, Shigella flexneri, and Salmonella typhi. were used as microbes test. Antidiarhhea activity was tested to diarrhea animal induced by castor oil. Dosage test was given one hour before induction then carried out observations of feces (frequency, consistency and weight). Transit intestinal method was also performed in this experiment with comparing the length of the intestinal through by marker with the total length of the intestine. Antidiarrhea activity result have shown that Harendong leaf extract at the doses 50 and 100 mg/kg BW showed decreased of frequency ,consistency and weight of feces better than another extract. Ethylacetate fraction of the leaf harendong showed antibacterial activity to Shigella dysenteriae ( MIC of 128 µg/ml), dan Salmonella typhi (MIC 512 µg/ml), and fraction n-heksan of the leaf harendong showed antibacterial activity to Shigella dysenteriae and Salmonella typhi the MIC 512 µg/ml.